The Attitudes Of Students Towards The Usage And Effect Of The Saudi Pidgin Arabic On the Saudi Society: Prince Sattam Bin Abdulaziz University As A Case Study - Haroon N. Alsager; Mohamed S. Aly (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The purpose of this study is to explore the attitudes of Saudi university students towards the usage and effect of Saudi Pidgin Arabic (henceforth SPA) on Saudi society. The study suggests social, cultural, and linguistic consequences of using Pidgin Arabic in Saudi Arabia. Showing these influences and exploring their effect on Saudi society is investigated by analyzing the attitudes of Saudi university students, with a particular emphasis on Prince Sattam bin Abdulaziz University students. Accordingly, the researcher utilizes the descriptive approach by using a questionnaire distributed to 440 Saudi male and female students at Prince Sattam bin Abdulaziz University. It was shown that the general tendency of the respondents to the Questionnaire is to hold the usage of such reduced contact language in low esteem for its possible harmful effects on the native tongue. They subscribe to the views that call for curbing such use and finding a solution for better communication with migrant workers and those coming in contact with them or even just interacting amongst themselves. This paper concludes that there should be Arabic courses for foreign workers who speak neither Arabic nor English, in order not only to maintain young people’s competence and performance in Standard Arabic, furthermore as a matter for enhancing their cognitive abilities, which are badly needed for competition in a world built on the power of knowledge.